THE INTELLIGENCE OF THE JEWISH NATION - Lydia Megawati (Universitas Islam Negeri Alauddin Makassar, 2021)
Understanding Judaism must be able to distinguish between two things, namely Judaism as a nation and Judaism as a religion. Jews as a nation known as a nation that is superior or superior to race or nation the other. This is not without reason and cause, the long journey of the Jews and the forgings of life that make them strong. The expulsion that occurs constantly being made the nation's Jews be spread in the whole world, the road to be able to still survive life is to have the skill and certainly intelligence to think. Intelligence that they have formed from the intake of food that has been observed since the age of the womb. The food that is consumed is always observed in many cases.